Species Richness and Nesting Sites of Stingless Bees in the Forest and Settlement Areas in Banten Province, Indonesia and their Morphometry - Atmowidi, Tri; Oktaviani, Widia Bela; Karimah, Khadijah Nurul; Prawasti, Taruni Sri; Dorly; Priawandiputra, Windra (Bogor Agricultural University, Indonesia, 2024)
Stingless bees (Apidae: Meliponinae) are distributed in the tropics, and there are more than 600 species worldwide, Forty-six species were recorded in Indonesia. Nest of the species is generally found in tree holes, rocks, house walls, house wooden, bamboo cavities, and soil. Current research explores the species richness, nesting sites and morphometry of stingless bee species in the forest and settlement areas in Banten province, Indonesia. Road- and purposive sampling methods were used to explore the stingless bee species. Thirty-five body characters of each stingless bee species were measured. Results showed four stingless bee species found were Tetragonula laeviceps, Heterotrigona itama, Lepidotrogona terminata, and Tetragonula sp. The dominant species found was L. terminata in the forest, while T. laeviceps in the settlement areas. The nesting sites of stingless bees in the forests were found in the tree cavities of various plant species with tree diameter range 39.3-87.3 cm. In contrast, the nest of T. laeviceps was found in the tree of Swietenia mahagoni, Lansium parasiticum, and bamboo cavities of houses in the settlement areas. The nest entrances of stingless bees varied, i.e., oval-rounded, tubular with varied diameters, and blackish-brown in color. The internal structure of the nest consists of brood cells, pollen cells, and honey cells. Heterotrigona itama has the largest body size (5.52 mm in length), followed by L. terminata (4.99 mm in length) and T. laeviceps (3.86 mm in length). Thirty-three characters of H. itama were larger than L. terminata and T. laeviceps, except for gena width and malar length.